Falsas denuncias por abuso sexual a menores de edad y el mal uso del tipo penal con la finalidad de obtener ingresos económicos - González Medina, Eliana del Cisne (2022)
The present research work is entitled "False accusations for sexual abuse of minors and the misuse of the criminal type with the purpose of obtaining economic income", which is interested in developing it arose because it is more and more frequent to observe how certain people, taking advantage of the social and legal awareness that the current society suffers in front of the crimes that violate the sexual integrity of people, try to favor themselves both morally and economically. From the study carried out it can be observed that there are unscrupulous people who take advantage of the social and juridical sensibility that sexual crimes generate in the social body, to obtain, most of the times, that the sentence issued by the judge be favorable to their cause, or even, they do not need to go to trial, since with the only fact of presenting the denunciation to the Prosecutor's Office, they already have the opportunity to psychologically manipulate the suspect so that he agrees to deliver a determined amount of money in exchange for not continuing to push forward the denunciation; They care little or nothing about the severe legal and social effects that await those who are falsely accused of committing this type of crime. In this thesis, materials and methods that facilitated the development of the research were applied, likewise, surveys and interviews were conducted with legal professionals, from which the necessary results were obtained to propose a legal reform project to the Organic Integral Penal Code; whose purpose is to incorporate in its article 170, a paragraph that establishes the definition of "acts of a sexual nature" in order to delimit the actions of people when they adapt their conduct to the criminal type of Sexual Abuse and to avoid an open interpretation of it